Pengaruh Beban Kerja dan Upah Kerja Terhadap Kinerja Karyawan Pada PT Jaya Utama Kota Tangerang - Indah Puspa; H. Jazuli Mukhtar (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to determine the effect of workload and wages on employee performance at PT Jaya Utama Tangerang City, both partially and simultaneously. Amidst intense industrial competition, human resource management has become a key factor in maintaining company productivity through appropriate workload management and fair compensation.The research method used is descriptive quantitative. The sampling technique employed is total sampling (saturated sampling), involving all 80 employees as respondents. Data were collected through questionnaires and analyzed using validity tests, reliability tests, classical assumption tests, descriptive analysis, coefficient of determination analysis (R2), and hypothesis testing (t-test and F-test).The results show that partially, workload has a significant effect on employee performance with a t > t table(2.672 > 1.991) and a significance value of 0.009 < 0.05. Similarly, wages also have a significant effect on employee performance with a tcoun > t table (7.856 > 1.991) and a significance value of 0.000 < 0.05. Simultaneously, workload and wages have a significant combined effect on employee performance, evidenced by an F > F table (74. 402 > 3.115) and a significance value of 0.000 < 0.05. The coefficient of determination analysis shows an R-Square value of $0.659$, indicating that workload and wages contribute 65.9% to employee performance, while the remaining 34.1% is influenced by other factors outside this study. In conclusion, workload and wages collectively have a siignificant impact on employee performance at PT Jaya Utama Tangerang City.